Analysis the Effect of Green Banking Implementation and Bank Efficiency on the Profitability of Sharia Commercial Banks in Indonesia - Ilen Marliani; Iman Waskito (Citakonsultindo, 2024)
This research aims to examine the effect of green banking and bank efficiency (BOPO) on profitability in Islamic commercial banks in Indonesia during the 2019-2023 period. The data used is secondary data from sharia commercial banks registered with the Financial Services Authority (OJK), with a sample consisting of 7 sharia banks selected through a purposive sampling method. Data analysis was carried out using the multiple regression method on panel data using Eviews 12 to understand the influence of the independent variable on the dependent variable. The research results show that partially, green banking has a significant positive effect on Return on Assets (ROA), while BOPO has a significant negative effect on ROA. Simultaneous testing found that the implementation of green banking as measured by GCR and BOPO together had a positive and significant influence on ROA. These findings indicate the importance of implementing green banking and operational efficiency in increasing the profitability of Islamic commercial banks in Indonesia.